Challenges and countermeasures of China’s research on “sports promoting adolescent socialization”–data mining based on Weibo and CNKI - Jiang, Yueyan; Tao, Baole; Lu, Tianci; Yan, Jun (Frontiers in Psychology, 2023)
Objective Understand the public demand for Adolescent socialization, and compare the hot spots in the researches of “sports promoting Adolescent socialization,” so as to clarify the high-quality development direction of sports promoting Adolescent socialization in the new era. Methods Collected the Weibo texts about “Adolescent socialization” from April 13, 2017 to June 1, 2022 through python, and used LDA to understand the relevant hot spots. Used City space to collect CNKI studies related to “sports promote Adolescent socialization,” and used keyword co-occurrence network to understand hot spots. Results A total of 77,900 original Weibo texts were captured. The theme model identified five potential themes: “School and Family Education,” “Social Participation,” “Community Education,” “Ideological and Political Education” and “Media.” The semantic network showed that the public concerns of each theme include “Adolescent socialization education content,” “relevant policies and regulations,” “Adolescent socialization environment,” “traditional culture” and “publicity ways and examples”0.52 studies were finally retrieved. The keyword co-occurrence network showed that keywords such as “Adolescent,” “Socialization,” “Sports Games,” “School Sports” and “Family Sports” appeared more frequently and had higher intermediary centrality. Researches focused on Socialization, Internet Addiction, Coupling, School Sports, Sports Socialization Media. Conclusion The public’s attention to “Adolescent socialization” has three characteristics: subject linkage, object susceptibility, and media diversity. The researches on “Sports Promoting the socialization of Adolescents” has some problems, such as the imbalance of subject supply and demand, the inconsistent way of object supply and demand, and the different content of media supply and demand. The reason is that there is an information island between people and scholars. Existing research results can not meet the demands of the public.